Hyperthermia-induced changes in leukocyte survival and phagocytosis: a comparative study in bovine and buffalo leukocytes - Scatà, Maria Carmela; Alhussien, Mohanned Naif; Grandoni, Francesco; Reale, Anna; Zampieri, Michele; Hussen, Jamal; De Matteis, Giovanna (Frontiers in Veterinary Science, 2024)
Heat stress negatively affects health, welfare, and livestock productivity by impairing immune function and thus increasing disease incidence. In recent years, there has been increasing interest in understanding the immune system of water buffalo due to the growing economic impact of this specie for the high quality and nutritional value of buffalo milk. The aim of this study was to compare the in vitro effect of hyperthermia on apoptosis and phagocytosis in leukocytes from bovine and buffalo species. For this, whole blood samples of six bovines and nine buffaloes were incubated at 39°C or at 41°C for 1, 2, and 4 hours. Two flow cytometric assays were then performed to evaluate apoptosis and determine phagocytic cells' functional capacity (neutrophils and monocytes). Results showed that the viability of bovine and buffalo leukocytes was differently affected by temperature and time of in vitro exposure. A higher percentage of apoptotic leukocytes was observed in bovines than in buffaloes at 39°C (P<0.05) and at 41°C (P<0.05) and for all incubation time points (P<0.05). In contrast, no difference was observed in the fraction of necrotic leukocytes between the two species. In both species, lymphocytes showed the highest sensitivity to hyperthermia showing an increased apoptosis rates along with increased incubation time. Although no significant differences were found between the two species regarding the percentage of phagocytic neutrophils, lower phagocytosis capacity values (MFI, mean fluorescence intensity) were found in bovines compared to buffaloes at 41°C (P>0.05). For monocytes, however, the differences between species were significant for both phagocytosis activity and capacity with lower percentages of bovine phagocytic monocytes after 2h at 39°C and after 1h at 41°C. The bovine monocytes showed lower MFI values for all temperature and time variations than buffaloes (37538.91 vs. 90445.47 at 39°C and 33752.91 vs. 70278.79 at 41°C, P<0.05). The current study represents the first report on the comparative analysis of the effect of in vitro heat stress on bovine and buffalo leukocyte populations highlighting that buffalos' leukocytes exhibit relatively higher thermal adaptation than bovine cells.